Nurse taking care and teaching to the family of the client with gastrostomy in home scene . Preview note - Vera Lúcia de Castro Périssé; Fátima Helena Espírito Santo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The client that suffered a gastrostomy needs the full attention of a stomaterapist nurse. This support starts with the feeding tube installation and should be followed in homecare attention by motivating the family to take part of this process, giving them the necessary support, teaching how to manage the feeding tube, how to handle it in the process of feeding the client and also the physical and emotional care required in order to prevent difficulties and contributing effectively to the health promotion, maintenance and rehabilitation of the client in the family scenario. The aim of this work is to know the new possibilities of innovation in the nurse's practice and teaching when attending the gastrostomy client's family, identifying the needs of the family in this kind of care in the family scenario and elaborating a homecare program to the family of a gastrostomy client. It is a qualitative research which will count with: a selection of clients submitted to gastrostomy in the Video-Endo Clinic; home visits evaluations by participative observation of the family scenario conditions to attend the clients´s needs; orientations with practical demonstrations of care actions with the client in nutritional support by gastrostomy, thorough the identification of the family's needs concerned the client care, by analyzing the interviews and observation, and the elaboration of a homecare program for these